Indeterminacy in a forward-looking regime-switching model - Roger E. A. Farmer; Daniel F. Waggoner; Tao Zha (Federal Reserve Bank of Atlanta, 2007)
This paper is about the properties of Markov-switching rational expectations (MSRE) models. We discuss possible solution concepts for MSRE models, distinguishing between stationary and bounded equilibria. For the case of models with one variable, we provide a necessary and sufficient condition for uniqueness of a bounded equilibrium, and we relate this condition to an alternative, the generalized Taylor principle suggested by Davig and Leeper. We provide examples of models with multiple bounded and multiple stationary equilibria which suggest that it may be more difficult to rule out nonfundamental equilibria in MSRE models than in the single-regime case where the Taylor principle is known to guarantee local uniqueness.
Keywords: E5; 330; policy rule; inflation; serial dependence; multiple equilibria; stationary equilibrium; bounded equilibrium